(untitled) - Gardner, Robert; 1929- (Berkeley Heights, NJ, 2000)
Explains how to perform a variety of magic tricks by using the laws of nature, including demonstrations of air pressure, optical illusions, chemical reactions, and more.
Includes bibliographical references (p. 124-125) and index.
Accelerated Reader AR
Keywords: Science projects; Juvenile literature; Magic tricks; Juvenile literature